Coercive persuasion as a specific type of violence in criminal law - Bardavío Antón, Carlos (International Journal of Coercion, Abuse, and Manipulation, 2025)
The field of cults, and that of destructive or coercive cults in particular, has received little attention from the perspective of criminal law doctrine. Supporters of such groups often claim to be victims of a violation related to freedom of will. In this article, I consider various methodologies and manipulation techniques used by such groups and suggest that comparative law, criminal definitions, and regulatory problems provide the basis for a more comprehensive understanding of criminal phenomenology that includes these concerns: the loss of freedom through coercive persuasion, and thus being the victim of a crime, or through becoming an instrument for the commission of crimes ordered by third parties. Research shows that the conventional definition of crime against freedom of will and physical injury is inadequate. I posit that a new approach to legal doctrine and criminal classification is required to fight against new crime phenomenology. I propose a criminal classification aimed at considering coercive persuasion as a crime, and a definition for the criminalization of certain organizations that engage in willful misconduct or reckless conduct.
Keywords: coercive control; coercive cults; coercive persuasion; psychic injury; criminal conspiracy